Odpowiedź :
Odpowiedź:
zad 3
a) 4x - 8y - 4z = 4(x - 2y - z)
6a - 9b + 12y = 3(2a - 3b +4y)
b) 63m + 54n - 9 = 9(7m + 6n - 1)
[tex]\frac{3a^{2} }{5} +\frac{6b}{5}-\frac{9}{5} =\frac{1}{5} (3a^{2} +6b-9)[/tex]
zad 4
3,5a + 0,7b - 14 = 7(0,5a + 0,1b - 2)
odp B
zad 5
a) [tex]\frac{3}{4} x+0,75y^{2} -\frac{1}{4}z^{3} =\frac{1}{4} (3x +3y^{2} -z^{3} )[/tex]
b) [tex]\frac{1}{3} a-\frac{2}{3} b^{2} +1\frac{1}{3} c^{3} =\frac{1}{3}(a-2b^{2} +4c^{3} )[/tex]
c) jest rozmazany
Szczegółowe wyjaśnienie:
Odpowiedź:
20b+6c=2(10b+3c)
14a-7= 2(7a-3,5)
9b+12= 3(3b+4)
12a2-8b= 3(4a2+2b)
1,6a-2,4c= 1,6(a-1,5c)
2,5a+0,5b= 0,5(5a+b)
2,1a2-2,8c2=2 (0,1 a2-0,8 c2)
2,4x2-1,6y=4 (0,6xa2-0,4 y)
3
4 (x-2y-z)
3 (2a-3b+4y)
9 (7m+6n-1)
3 (a2+2b-3) /5
4
B 0,7 (5a+0,1b-20)
5
a) ¼ (3x+3y2-z3)
b) 1/3 (a-2b2+4c3)
Szczegółowe wyjaśnienie:
Nie widać dobrze c, załącz do innego pytania